Signifikansi Pendidikan Anak Dalam Perspektif Alkitab - Maria Lidya Wenas; I Putu Ayub Darmawan (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2017)
Maria Lidya Wenas & I Putu Ayub Darmawan,Â Significance Children Education in Biblical Perspective. Education of children is important in human life. Formulation of the problem in this research is how the Bible perpsektif about children's education? The purpose of this study is to outline perpsektif Bible about children's education. Types of research in this paper is the qualitative research literature. The object of this study is a biblical perspective on the education of children. In this study, researchers conducted a literature study to be able to explore and understand the biblical view of children's education. In this study, the authors sought feedback from a grasp of Hebrew and Greek. This is to avoid the use of verses in Hebrew and Greek avoid deviations. From this study showed that (1) Education of children as the planting of faith; (2) Education of children as a process of knowledge transfer; (3) the child's education as a process of value investment.